The Economic Consequences of Weintraub's Consumption Coefficient - Douglas Mair; Anthony J. Laramie; Jan Toporowski (Levy Economics Institute of Bard College, 1994)
In this paper we show that Weintraub:s consumption coefficient (the ratio of total consumption to wages) can elucidate trends in the sectoral and functional distributions of income We also show that, in a Kaleckian model, it simplifies and add precision to Kaleckian macroeconomics. Using a Kaleckian definition of profits, empirical estimates of the coefficient are presented for the UK 1972-1990. From a level of around 1.1 in the 1970 s, the coefficient rose to around 1.3 in the mid-1980s from which it has started to fall back to its 1970's levels. During the 1980s, the coefficient indicated a marked redistribution of income in favour of profits along with a rise in capitalists' propensity to consume. This confirms the evidence that the economic boom of the 1980s was driven principally by an expansion of demand for luxury goods rather than fixed capital investment. This will have been a factor in the slump after 1990.
Keywords: 330